Polyamic acid (PAA) immobilized on glassy carbon electrode (GCE) as an electrochemical platform for the sensing of tuberculosis (TB) antibodies and hydrogen peroxide determination. (2nd January 2020) - Ngema, Xolani Terrance; Baker, Priscilla; Ajayi, Fanelwa; Aubert, Pierre-Henri; Banet, Philippe
Abstract: Tuberculosis (TB) is a chronic infectious disease that usually affects the pulmonary region of human beings. It remains critically important to develop cost effective methods for TB detection, especially since impoverished communities are often the target population. Immunological assays are commonly used for the detection of TB and are typically based on selected antibody (Ab) antigen (Ag) interactions as measured by the enzyme-linked immunosorbent assay (ELISA). It is also common to have tagged antibody/antigen binding pairs where the signaling is produced by the tag as is the case with the indirect tuberculosis IgG ELISA Kit, where a horseradish peroxidase (HRP) tag on the antibody is responsible for the analytical signal. Mycobacterium tuberculosis (MTB), recombinant protein antigen 85B (Ag85B), is the most abundant protein exposed by Mycobacterium tuberculosis acting as a potent immuno-protective antigen. In this work, both Ag85B and antibody-HRP (Ab-HRP) were immobilized on a semi-conductive polyamic acid (PAA) electrochemical interface towards the design of new electrochemical sensors. In a first approach, the antigen, Ag85B, was employed as the bioreceptor to afford label-free TB signaling through antibody detection and the obtained limit of detection was 8 μg/mL of antibody. The response was evaluated by voltammetric methods and electron impedance spectroscopy (EIS). Cyclic voltammetry (CV) and EIS were used to characterize the charge transfer and capacitive behavior of the label-free sensor. In a second approach, the HRP tagged antibody was used for the design of a stable hydrogen peroxide (H2 O2 ) sensor with very good analytical performance with a limit of detection equal to 1.3 μM. Even though we developed an ultrasensitive H2 O2 sensor, no further development of TB antigen detection was possible in this work.